Canadian Thoracic Society Asthma Management Continuum – 2010 Consensus Summary for Children Six Years of Age and Over, and Adults - M Diane Lougheed (Canadian Respiratory Journal, 2010)
BACKGROUND/OBJECTIVE: To integrate new evidence into the Canadian Asthma Management Continuum diagram, encompassing both pediatric and adult asthma.